INTEGRASI NILAI-NILAI KEARIFAN LOKAL MASYARAKAT KEFAMENANU DAN NASIONALISME DALAM PEMBELAJARAN SEJARAH (STUDI PADA SMAN NOEMUTI) - Sabu, Omiano; Sunardi, S.; Joebagio, Hermanu (Sebelas Maret University (UNS), 2016)
This research was conducted from April to June 2016 in SMAN (Noemuti Public Senior High School of Noemuti). This school implemented local wisdom traditional art as teaching material in History subject corresponding to Education Unit Level Curriculum (KTSP 2006) containing the social-cultural characteristics of local community. This research aimed: (1) to identify the local wisdom values of Kefamenanu community, 2) to find out the historical learning plan based on the local wisdom values of Kefamenanu community, 3) to find out the implementation of historical learning based on the local wisdom values of Kefamenanu community, 4) to find out the evaluation process of history learning based on the local wisdom and nationalism values in SMA Noemuti; and 5) to find out the constraints encountered in the implementation of local wisdom values of Kefamenanu community in History Learning.The method employed in this research was descriptive one with qualitative approach. Technique of analyzing data used was an interactive analysis one encompassing data reduction, data display and conclusion drawing. History and local wisdom values taught to the 10th graders of SMAN Noemuti is a preservation of cultural values because the history teacher inspires and motivates the students in order to find out and to understand the values contained in history learning. The results of research showed that: 1) martial dance art was not only a performing art or an entertainment, but it also contained of many moral messages and cultural values. The values contained in local wisdom included: (a) education, (b) religious/sacred, (c) custom/tradition, (d) creativity, (d) social care, and (f) commercial values. 2) In planning the history learning, the teacher referred to curriculum (KTSP 2006) to develop syllabus. Then, it was explained in RPP. 3) The implementation of local wisdom values exerted positive effect in which the students could understand the history of local wisdom development and the values contained within it. 4) The evaluation was emphasized on three aspects: cognitive, affective, and psychomotor aspects, 5) the constraints encountered were related to limited time allotment (only 45 minutes/meeting). The alternative way to deal with the constraints was to give the learning material first to the students aiming to make the students able to learn the material taught before the next week meeting.Â